The nutcracker and the four realms [videorecording (DVD)] - Foy, Mackenzie, 2000-; Knightley, Keira, 1985-; Freeman, Morgan; Syal, Meera; Macfadyen, Matthew, 1974-; Hoffmann, E. T. A. (Ernst Theodor Amadeus), 1776-1822 (Disney DVD., 2019)
In search of a key to unlock a box from her late mother, Clara finds her way into a mysterious parallel world. She teams up with a soldier named Philip in order to brave the Fourth Realm to find the key and return harmony to the unstable world.